A study of the matching of impellers and motors for contra-rotating fan based on electromagnetic-fluid coupling analysis. (November 2016) - Wang, Qian; Meng, Dawei
The contra-rotating fan is an electromechanical device in which electromagnetic force and aerodynamic force coordinate together. Its operation process is affected by multiple factors and is also coupled with multiple variables. In order to further reveal its working mechanism, electromagnetic-fluid coupling model for contra-rotating fan was presented and relevant numerical computations were performed by the combination of the motors' electromagnetic-field simulation and the fan's fluid-field simulation. Curves of electromagnetic torque and aerodynamic torque in time domain, respectively, for two motors and two impellers of the fan were obtained, and then fast Fourier transform algorithm was used to analyze their harmonic components. Meanwhile, the resonance effect induced by the same-frequency components between the harmonic electromagnetic and aerodynamic torques was investigated. Moreover, the impeller–motor interaction and matching performance were explored so as to determine the optimal combination scheme of blade number in two-stage impellers. The reasonableness of this scheme was validated experimentally. This heterogeneous physical-field simulation method targeted at electromagnetic-fluid coupling condition offers an important reference for optimizing the fan system.